KNOWLEDGE, ATTITUDE AND PRACTICES RELATED TO WATER QUALITY AND FISH PARASITES AMONG RESIDENCE COMMUNITIES OF WARWADE RESERVOIR DUTSE, JIGAWA STATE, NIGERIA - Miga, Hamisu Idris; Bichi, Armaya’u Hamisu; Dauda, Akeem Babatunde (FUDMA Journal of Sciences, 2025)
Indigenous knowledge, attitudes, and practices (KAP) about fish parasitic and water quality parameters are poorly understood, such information is essential for preventive and sustainable management of water bodies. A community based cross-sectional study was carried out to assess the knowledge, attitudes, and practices (KAPs) of the resident communities of Warwade reservoir on water quality and fish parasites. One hundred and twenty questionnaires were administered to the respondents from the three randomly selected locations (Warwade, Zuwan-hawa and Tsauni-arewa) around the water body. The data was presented using descriptive statistics. The result showed that most of the respondents were aged between 21-30 years, representing 31.67%. Gender participation indicated that 66.67% of the respondent were male. The respondents in this study had a good level of knowledge on changes of the water quality of the reservoir, with a mean score of 68.33% with 75% of the participants had insufficient knowledge of entering pollutant/sewage into the reservoir. Some believed (41.67%) the pollutants are from agricultural and domestic wastes. Majority of the respondents (84.17%) had insufficient knowledge of fish parasites, while 75% strongly believed fish parasites is harmful for health. Majority (60%) of the respondents had sufficient knowledge that eating undercook fish/raw can result in acquiring fish parasites while 87.5% of the respondents had bad attitude and practice of washing their clothes in the reservoir and 81.66% swim/bath/paly around the reservoir. The study recommended health education activities in the communities, in order to change the perception of risks associated with changes of water quality and...
Keywords: Attitude; Fish parasites; Knowledge; Practices; Water Quality; Warwade